Work Disutility and Compensating Differentials: Estimation of Factors in the Link between Wages and Firm Size - Dunn, L. F. (The Review of Economics and Statistics, 1986)
This paper investigates the positive wage-firm size relationship using a sample of workers performing the same jobs in different-sized firms. Controlling for skill differences, wages are still found to be higher in larger firms. Using an estimate of the marginal rate of substitution of income for leisure as a measure of job disutility, the difference in wages between large and small firms is found to be greater than the difference in disutility, ruling out compensating differentials as the sole cause of the wage-size relationship. Hence the argument that labor extracts some of the higher profits of larger firms is plausible.